2002
DOI: 10.1515/jpem.2002.15.7.1017
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Rickets in Saudi Arabia: A Rich and Sunny Country

Abstract: In this retrospective study from Saudi Arabia, which is a rich and sunny country, we report our experience with 34 adolescents (20 females, 10 males) with rickets. The commonest cause was vitamin D deficiency (58.8%) followed by rickets due to low calcium intake (11.8%) and genetic causes, including possible 25-hydroxylase deficiency (8.8%). The etiology of nutritional rickets is multifactorial, including lack of sun exposure and inadequate calcium intake. The clinical symptoms were nonspecific and therefore c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 10 publications
(15 reference statements)
2
32
1
1
Order By: Relevance
“…Baroncelli et al(2008) showed that the VDR B allele may predispose to vitamin D deficiency . Moreover, it has been reported that greater than usual doses of vitamin D are needed to cure rickets in children of the Middle East (Essawy et al, 1992;Abdullah et al, 2002). However, in view of the lack of difference of serum 25-OHD levels between different VDR genotypes in our study, we cannot conclude that vitamin D status in our population is regulated by VDR polymorphisms.…”
Section: Discussioncontrasting
confidence: 60%
“…Baroncelli et al(2008) showed that the VDR B allele may predispose to vitamin D deficiency . Moreover, it has been reported that greater than usual doses of vitamin D are needed to cure rickets in children of the Middle East (Essawy et al, 1992;Abdullah et al, 2002). However, in view of the lack of difference of serum 25-OHD levels between different VDR genotypes in our study, we cannot conclude that vitamin D status in our population is regulated by VDR polymorphisms.…”
Section: Discussioncontrasting
confidence: 60%
“…We can thus state that the brief and casual exposure of the face, arms and hands to sunlight may not provide certain individuals with their vitamin D requirements, and also that the garments limit exposure to sunlight. This is in agreement with the data reported by Alagol (12), and Abdullah (13) in Turkish and Saudi Arabian women who, due to covering their bodies with clothing, usually have low serum 25OHD concentrations.…”
Section: Discussionsupporting
confidence: 93%
“…This lifestyle makes Middle Easterners vulnerable even in the United Kingdom 2-5 and in America [6][7][8] . In addition, it has been suggested that a genetic factor (25-hydroylase deficiency) may be responsible for the increased incidence of NR in this community 9 . The increased incidence of NR in male children (71.64%) in our study has also been noticed in other studies.…”
Section: Discussionmentioning
confidence: 97%